Cultural Depictions of Bugis-Makassar Wedding Traditions in the Novel “Mahar Dari Langit” - Whida Rositama (Bulletin of Science Education, 2024)
A novel, as one of literary works, frequently depicts the real life situation. One of the conditions is cultural. This study aims to demonstrate how Bugis-Makassar marriage culture represented in Mahar dari Langit novel. It is crucial to be analyzed because by finding Bugis culture through novel, people do not need to experience it directly by themselves associated with the real condition there, whether it is good or negative. The researcher analyzes the data using a qualitative method and representation theory. The results indicate that the Mahar dari Langit novel represents Uang Panai' which can be paid by the prospective bride's father. Furthermore, this novel represents the progress of getting married in Bugis in five steps only; they are Mammanu' manu', Mappese' pese', Mappetu Ada, Mappaere Botting, and Mapparola.